Solve for y az+by=c

Math
az+by=c
Subtract az from both sides of the equation.
by=c-az
Divide each term by b and simplify.
Tap for more steps…
Divide each term in by=c-az by b.
byb=cb+-azb
Cancel the common factor of b.
Tap for more steps…
Cancel the common factor.
byb=cb+-azb
Divide y by 1.
y=cb+-azb
y=cb+-azb
Move the negative in front of the fraction.
y=cb-azb
y=cb-azb
Solve for y az+by=c

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top